Unconventional Monetary Policy, Fiscal Side Effects and Euro Area (Im)balances - Michael Hachula; Malte Rieth; Michele Piffer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We study the effects and transmission channels of non-standard monetary policy in the euro area using structural vector autoregressions, identified with an external instrument. The instrument is the common component of unexpected variations in euro area sovereign yields vis-à-vis Germany for different maturities on policy announcement days. We find that expansionary monetary surprises are effective in stimulating economic activity, prices and inflation expectations. Shock transmission functions through public and private interest rates, asset prices and credit conditions. The policy innovations, however, also lead to a rise in primary public expenditures, a divergence of relative prices within the union and a widening of internal trade balances.
Keywords: E52; E58; E63; 330